The role of the rhizobiome recruited by root exudates in plant disease resistance: current status and future directions - Zengwei Feng; Qiuhong Liang; Qing Yao; Yang Bai; Honghui Zhu (Environmental Microbiome)
Abstract Root exudates serve as a bridge connecting plant roots and rhizosphere microbes, playing a key role in influencing the assembly and function of the rhizobiome. Recent studies have fully elucidated the role of root exudates in recruiting rhizosphere microbes to enhance plant performance, particularly in terms of plant resistance to soil-borne pathogens; however, it should be noted that the composition and amount of root exudates are primarily quantitative traits regulated by a large number of genes in plants. As a result, there are knowledge gaps in understanding the contribution of the rhizobiome to soil-borne plant disease resistance and the ternary link of plant genes, root exudates, and disease resistance-associated microbes. Advancements in technologies such as quantitative trait loci (QTL) mapping and genome-wide association studies (GWAS) offer opportunities for the identification of genes associated with quantitative traits. In the present review, we summarize recent studies on the interactions of plant and rhizosphere microbes through root exudates to enhance soil-borne plant disease resistance and also highlight methods for quantifying the contribution of the rhizobiome to plant disease resistance and identifying the genes responsible for recruiting disease resistance-associated microbes through root exudates.